Board Gender Diversity and Corporate Social Responsibility. A Literature Review on Critical Mass Theory and Research Recommendations - Velte, Patrick (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
This study addresses the question of whether a critical mass of female directors positively contributes to corporate social responsibility (CSR) outcomes. Based on stakeholder‐agency and critical mass theories, a structured literature review of 92 archival critical mass studies on the impact of board gender diversity (BGD) on CSR performance and reporting was conducted. Separating absolute and relative measures of critical mass, country‐specific studies were also grouped according to board structures and board gender quotas of respective regimes. The review indicates a positive impact of at least three female directors on CSR outcomes. This relates to cross‐country studies as well as to countries with a one‐tier system. Interestingly, the positive relationship between at least three women on boards and CSR relates to countries with voluntary and mandatory board gender quotas. To the best of our knowledge, this paper presents the first literature review with a focus on critical mass theory in BGD and CSR, as it structures the main variables that have been recognized in prior studies, stresses key research gaps, and presents major recommendations for future research. Among others, future studies should address potential moderators and recognize interactions with other board characteristics. The study is also highly relevant for regulatory bodies and business practice to recognize a critical mass of female directors for listed companies.
Keywords: Board Gender Diversity; Board Systems; Corporate Governance; Critial Mass Theory; CSR Performance; CSR Reporting